2012
DOI: 10.1051/0004-6361/201219719
|View full text |Cite
|
Sign up to set email alerts
|

Low-mass planets in nearly inviscid disks: numerical treatment

Abstract: Context. Embedded planets disturb the density structure of the ambient disk, and gravitational back-reaction possibly will induce a change in the planet's orbital elements. Low-mass planets only have a weak impact on the disk, so their wake's torque can be treated in linear theory. Larger planets will begin to open up a gap in the disk through nonlinear interaction. Accurate determination of the forces acting on the planet requires careful numerical analysis. Recently, the validity of the often used fast orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…We also vary the power-law indices p, q to examine the effect of the background potential vorticity and dust-to-gas ratio profiles, and consider the effect numerical resolution. Kley et al (2012). We use NR cells logarithmically spaced in R and N φ cells uniformly spaced in φ.…”
Section: Dusty Disc-planet Interactionmentioning
confidence: 99%
“…We also vary the power-law indices p, q to examine the effect of the background potential vorticity and dust-to-gas ratio profiles, and consider the effect numerical resolution. Kley et al (2012). We use NR cells logarithmically spaced in R and N φ cells uniformly spaced in φ.…”
Section: Dusty Disc-planet Interactionmentioning
confidence: 99%
“…Note that setting the boundary conditions to open has no significant effect on the results but increases the computational time due to waves developed near the inner boundary. In planet-bearing models, we use H a  ( ) as the smoothing of the gravitational potential of the planet with an appropriate value of 0.6  = (Kley et al 2012). In our simulations, the star is always at the center of the numerical domain.…”
Section: Hydrodynamic Modelsmentioning
confidence: 99%
“…However, by their nature 2D simulations can not include information about the vertical dynamics or the dynamics of the material above over below the planet. Analysis and simulations of discs by Müller et al (2012) and Kley et al (2012) showed that in order for the results from 2D simulations to be in agreement to their 3D counterparts, the softening parameter for the gravitational potential (Eqn. 3) must be increased to = 0.7H when self-gravity is not taken into consideration.…”
Section: Simulation Setupmentioning
confidence: 91%